Effects of Manual Communication Method on Listening Proficiency of Students with Hearing Impairment in Special Schools in Lafia Metropolis, Nasarawa State, Nigeria - Andrew Yakubu; Terkula Joseph (Goodwood Publishing, 2026)
Purpose: This study aimed to investigate the effects of manual communication methods on the listening proficiency of students with hearing impairment in special schools in Lafia Metropolis, Nasarawa State, Nigeria. Research Methodology: A quasi-experimental design was used with 57 students with hearing impairment from two schools in Malaysia. The experimental group (n=15) received instruction using the manual communication method, including sign language, finger spelling, gestures, and visual cues, while the control group (n=14) received oral communication instruction emphasizing speech and lip reading. Listening proficiency was measured using a validated 100-mark Listening Proficiency Assessment Tool, with a Cronbach's alpha reliability coefficient of 0.82. Data were analyzed using t-tests and two-way analyses of variance. Results: The experimental group significantly outperformed the control group in post-test scores (M = 72.40, SD = 8.30) vs. (M = 58.20, SD = 7.90), with a large effect size (Cohen's d = 1.76). Age of hearing loss onset and parental communication mode influenced the effectiveness of communication methods. Conclusions: Manual communication significantly enhances listening proficiency among students with hearing impairment and should be prioritized in special schools. Teacher training programs should integrate comprehensive manual communication instructions. Limitations: The study's limitations include a small sample size and focus on a single geographic area. Contributions: This study highlights the effectiveness of manual communication in improving listening proficiency among students with hearing impairment and emphasizes the need for targeted teacher training.